The Rights of the Illegitimate Child Under Perspectives of Shariah Law in Selected States in Malaysia - Che Ku Nur Syazwani Wahidah Che Ku Amran; Muhammad Firdaus Ab Rahman (Faculty of Syariah and Law, Universiti Sains Islam Malaysia, 2026)
The issue of an illegitimate child is a pressing matter for the Muslim community in Malaysia. Due to the stigma of society mostly denied the rights of an illegitimate child and though that an illegitimate child does not have the rights like legitimate child received. The fact is an illegitimate child have their own right that has been stated in Islam under the state provisions of Islamic Family Law Act 1984. Consequently, this research intends to examine Shariah regulations and the rights of an illegitimate child and also to analyse the challenges and resolution of the rights of an illegitimate child in Malaysia. This research uses a qualitative research method, collecting data from the research through journals, articles, legal acts, fatwa websites in Malaysia and recent studies or thesis. The findings indicate the issue of an illegitimate child, which is an illegitimate child have their own rights according to Shariah law in Malaysia. The expected outcome is to expose an illegitimate child and society regarding the rights of illegitimate child with the existence of regulations and to help an illegitimate child realize their own rights that entitled to them like other people.